Algebra


  1. If x +
    1
    = 66 , then the value of
    x2 + x + 2
    is
    xx2( 1 - x )










  1. View Hint View Answer Discuss in Forum

    ⇒ x +
    2
    = 1
    x

    Expression =
    x2 + x + 2
    =
    [ x + 1 + ( 2 / x ) ]
    x2( 1 - x )x( 1 - x )

    (Dividing numerator and denominator by x)
    Expression = x +
    2
    =
    [ x + 1 + ( 2 / x ) ]
    x2( 1 - x )x( 1 - x )

    Expression =   x +
    2
    + 1
    x
    x( 1 - x )

    Expression =
    1 + 1
    2 ×
    2
    x

    Expression =
    2
    = 1
    2

    Correct Option: A

    ⇒ x +
    2
    = 1
    x

    Expression =
    x2 + x + 2
    =
    [ x + 1 + ( 2 / x ) ]
    x2( 1 - x )x( 1 - x )

    (Dividing numerator and denominator by x)
    Expression = x +
    2
    =
    [ x + 1 + ( 2 / x ) ]
    x2( 1 - x )x( 1 - x )

    Expression =   x +
    2
    + 1
    x
    x( 1 - x )

    Expression =
    1 + 1
    2 ×
    2
    x

    Expression =
    2
    = 1
    2


  1. If p = 99, then the value of p(p2 + 3p + 3) is









  1. View Hint View Answer Discuss in Forum

    Using Rule 8,
    p = 99 (Given)
    ∴ p(p2 + 3p + 3) = p3 + 3p2 + 3p
    = p3 + 3p2 + 3p + 1 - 1
    = (p + 1)3 - 1 = (99 + 1)3 - 1
    ∴ p(p2 + 3p + 3) = 1003 – 1 = 999999

    Correct Option: C

    Using Rule 8,
    p = 99 (Given)
    ∴ p(p2 + 3p + 3) = p3 + 3p2 + 3p
    = p3 + 3p2 + 3p + 1 - 1
    = (p + 1)3 - 1 = (99 + 1)3 - 1
    ∴ p(p2 + 3p + 3) = 1003 – 1 = 999999



  1. Find the value of √(x² + y² + z)(x + y - 3z) ÷ ³√xy³z² when x = + 1, y = –3, z = – 1.









  1. View Hint View Answer Discuss in Forum

    Expression =
    (x² + y² + z)(x + y - 3z)
    = 1
    ³√xy³z²

    Putting x = 1, y = –3, z = –1
    Expression =
    (1 + 9 - 1)(1 - 3 + 3)
    = 1
    ³√ 1 × (-27) × 1

    Expression =
    3
    = -1
    -3

    Note : Original question is :
    (x² + y² + z)(x + y - 3z) ÷ ³√xy³z²
    which gives answer = – √7 which is not in options.

    Correct Option: C

    Expression =
    (x² + y² + z)(x + y - 3z)
    = 1
    ³√xy³z²

    Putting x = 1, y = –3, z = –1
    Expression =
    (1 + 9 - 1)(1 - 3 + 3)
    = 1
    ³√ 1 × (-27) × 1

    Expression =
    3
    = -1
    -3

    Note : Original question is :
    (x² + y² + z)(x + y - 3z) ÷ ³√xy³z²
    which gives answer = – √7 which is not in options.


  1. The simplest form of the expression
    ( p² - p )
    ÷
    ( p² - 1 )
    ÷
    is
    2p³ + 6p²p² + 3pp + 1









  1. View Hint View Answer Discuss in Forum

    Expression =
    ( p² - p )
    ÷
    ( p² - 1 )
    ÷
    2p³ + 6p²p² + 3pp + 1

    Expression =
    p( p - 1 )
    ÷
    ( p + 1 )( p - 1 )
    ÷
    2p²( p + 3 )p( p + 3 )( p + 1 )

    Expression =
    p( p - 1 )
    ×
    p( p + 3 )
    ×
    ( p + 1 )
    2p²( p + 3 )( p + 1 )( p - 1 )

    Expression =
    1
    2p²

    Correct Option: B

    Expression =
    ( p² - p )
    ÷
    ( p² - 1 )
    ÷
    2p³ + 6p²p² + 3pp + 1

    Expression =
    p( p - 1 )
    ÷
    ( p + 1 )( p - 1 )
    ÷
    2p²( p + 3 )p( p + 3 )( p + 1 )

    Expression =
    p( p - 1 )
    ×
    p( p + 3 )
    ×
    ( p + 1 )
    2p²( p + 3 )( p + 1 )( p - 1 )

    Expression =
    1
    2p²



  1. If x +
    1
    = 2 , then the value of x2 +
    1
    x3 +
    1
    is
    xx2x3










  1. View Hint View Answer Discuss in Forum

    ⇒ x +
    1
    = 2
    x

    On squaring both sides,
    ⇒ x2 +
    1
    + 2 = 4
    x2

    ⇒ x2 +
    1
    = 4 – 2 = 2
    x2

    Again , x +
    1
    = 2
    x

    On cubing both sides,
    x +
    1
    3 = 8
    x

    ⇒ x3 +
    1
    + 3x +
    1
    = 8
    x3x

    ⇒ x3 +
    1
    = 8 - 3 × 2 = 2
    x3

    x2 +
    1
    x3 +
    1
    = 2 × 2 = 4
    x2x3

    Second Method :
    Using Rule 14,
    Here, x +
    1
    = 2
    x

    x2 +
    1
    = 2 and x3 +
    1
    = 2
    x2x3

    x2 +
    1
    x3 +
    1
    = 2 × 2 = 4
    x2x3

    Correct Option: B

    ⇒ x +
    1
    = 2
    x

    On squaring both sides,
    ⇒ x2 +
    1
    + 2 = 4
    x2

    ⇒ x2 +
    1
    = 4 – 2 = 2
    x2

    Again , x +
    1
    = 2
    x

    On cubing both sides,
    x +
    1
    3 = 8
    x

    ⇒ x3 +
    1
    + 3x +
    1
    = 8
    x3x

    ⇒ x3 +
    1
    = 8 - 3 × 2 = 2
    x3

    x2 +
    1
    x3 +
    1
    = 2 × 2 = 4
    x2x3

    Second Method :
    Using Rule 14,
    Here, x +
    1
    = 2
    x

    x2 +
    1
    = 2 and x3 +
    1
    = 2
    x2x3

    x2 +
    1
    x3 +
    1
    = 2 × 2 = 4
    x2x3